A new Chinese Mesozoic dragonfly clarifies the relationships between Rudiaeschnidae and Cymatophlebiidae (Odonata: Aeshnoptera) - Li, Yongjun; Nel, André; Ren, Dong; Zhang, Binglan; Pang, Hong (Zootaxa, 2011)
A very well preserved fossil specimen of Rudiaeschna limnobia Ren and Guo, 1996, is described and diagnosis for Rudiaeschna is emended. Its clear morphological structures, including body characters, clarify and confirm the affinities of Rudiaeschna and the Rudiaeschnidae with Cymatophlebia Deichmüller, 1886, and the Cymatophlebiidae, previously inferred only through venational characters.